MAKING CHLORINE DIFFUSER IN REDUCING COLIFORM NUMBERS IN THE WELLS - Sanredja Kuswanto; Saudin Yuniarno; Ima Hastawati (Kesmas Indonesia, 2021)
Abstract The research location is in RW 6, Grendeng Village, which is a fairly slum area, with a total of 4 RTs, which are categorized as Slum Areas of My 2016/2017 Program. The problems in Grendeng village include population density, very tight housing distance, poor sanitation and clean water supply, latrine distance with dug wells so that the quality of the dug well water is mainly affected by its bacteriological quality. Countermeasures against these problems by disinfection of the dig wells with a Chlorine Diffuser. The analysis carried out on the experimental data in the study is the univariate test to determine the frequency of environmental quality around the dug wells and further analysis using the Paired T Test to determine the effectiveness of using a chlorine diffuser. Based on the results of the normality test analysis obtained a value of α = 0.457, the value of this normality is greater than the value of α 0.05. Then this test is continued by using the paired T Test. From the paired T Test, the probability value of α = 0,000 was obtained. So it can be concluded that there is an effect of decreasing the number of coliform bacteria by using a Chlorine Diffuser.